2002
DOI: 10.1038/sj.ijir.3900909
|View full text |Cite
|
Sign up to set email alerts
|

Is sildenafil failure in men after radical retropubic prostatectomy (RRP) due to arterial disease? Penile duplex Doppler findings in 174 men after RRP

Abstract: Sildenafil is frequently the first-line treatment for post-radical retropubic prostatectomy (RRP) erectile dysfunction (ED) with maximum treatment satisfaction rates of 43% -80%. The etiology of erectile dysfunction after RRP has been attributed to psychogenic, vascular, veno-occlusive or nerve injury causes. The purpose of this study was to gain insight into the penile duplex Doppler arterial parameters in men with ED after RRP who failed sildenafil. The purpose was to assess whether sildenafil failure after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Using a PSV < 30 cm/s and EDV ≤ 5 cm/s as the diagnostic criteria, our data also showed a low incidence of arterial insufficiency in both non-responders and responders (23.7% and 12.9%, respectively). This finding was comparable to the results of a previous study by McCullough et al [10]. In the aforementioned study, a low incidence of arterial insufficiency (19%) in sildenafil non-responders receiving nerve-sparing radical prostatectomy using a PSV < 25 cm/s as the diagnostic criteria was also noted.…”
Section: Discussionsupporting
confidence: 91%
“…Using a PSV < 30 cm/s and EDV ≤ 5 cm/s as the diagnostic criteria, our data also showed a low incidence of arterial insufficiency in both non-responders and responders (23.7% and 12.9%, respectively). This finding was comparable to the results of a previous study by McCullough et al [10]. In the aforementioned study, a low incidence of arterial insufficiency (19%) in sildenafil non-responders receiving nerve-sparing radical prostatectomy using a PSV < 25 cm/s as the diagnostic criteria was also noted.…”
Section: Discussionsupporting
confidence: 91%
“…In another, smaller trial, treatment with a statin for up to 12 weeks significantly improved EF (increase in EF domain score = 7.8; p = 0.04), and the clinical benefits of statins on EF were observed as early as treatment week 6 (140). Nightly treatment with a PDE5 inhibitor has also been shown to be effective in enhancing EF in patients with arteriogenic ED (141); many patients with inadequate responses to PDE5 inhibitors after prostatectomy have arterial insufficiency (142,143). Certain studies have suggested that enhanced control of cardiovascular risk factors and/or statin treatment may increase the efficacy of PDE5 inhibitors (vs. placebo + PDE5 inhibitors) (144,145).…”
Section: Resultsmentioning
confidence: 99%
“…5 Patients with a history of pelvic surgery or diabetes mellitus, for example, show a reduced level of response to sildenafil (eg 40-60%). [6][7][8] Approximately 50% of men who receive a prescription for sildenafil discontinue use of the drug over time. 9 Among other factors, side effects such as headache, flushing and changes in color vision are often cited as reasons for discontinuation of use.…”
Section: Introductionmentioning
confidence: 99%